Descriptive Analysis of Islamic Entrepreneurship Characteristics: A Quantitative Study of MSME Actors in South Kalimantan - Rusdina Rusdina; Dina Hermina; Nuril Huda (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2025)
This study aims to analyze and map the level of application of Islamic entrepreneurship (IE) characteristics among Micro, Small, and Medium Enterprises (MSMEs) actors in South Kalimantan. As a pillar of the regional economy, MSMEs in South Kalimantan, which are predominantly Muslim, face the challenge of aligning business practices with Shariah values while also addressing stagnating innovation and local employment dynamics. This research employs a descriptive quantitative approach. Primary data were collected through a questionnaire distributed to 100 Muslim MSME actors in South Kalimantan, selected using purposive and convenience sampling techniques. The research instrument was developed based on five IE dimensions: Shiddiq (Honesty), Amanah (Trustworthiness), Tabligh (Transparency), Fathanah (Competence), and Spirituality. Data were analyzed using descriptive statistics to identify mean scores and levels of implementation. The results show differing profiles of implementation across dimensions. The Spirituality, Shiddiq, and Amanah dimensions exhibit a "Very High" level of implementation, indicating that personal ethics and spirituality have been strongly internalized. In contrast, the Fathanah dimension (particularly indicators of orderly administration and innovation) and the Tabligh (transparency) dimension fall into the "Moderate" category. These findings reveal a strategic gap: high individual piety (the religio-economic spirit) has not been effectively translated into professional managerial competence (human capital). This is relevant to macroeconomic data from BPS as of August 2025, which reported an Open Unemployment Rate (TPT) of 4.20% and a dominance of the informal sector (53.56%), as well as data from the Regional Office of the Directorate General of Budget Financing (Kanwil DJPb) of South Kalimantan, showing that although the realization of KUR (People's Business Credit) disbursement reached a massive Rp3.34 trillion (as of July 2025), growth barriers for MSMEs have shifted from access to capital toward human resource capacity. The practical implication of these findings is the need for policy intervention, particularly from related agencies in South Kalimantan, to focus MSME training on improving managerial competence (Fathanah) and Akhlak-based soft skills rather than solely on spiritual motivation or capital assistance